Joker: um realizador de desenhos animados para linguagens formais - Souza, Diego Henrique Oliveira de (2011)
Using formal methods, the developer can increase software s trustiness and correctness. Furthermore, the developer can concentrate in the functional requirements of the software. However, there are many resistance in adopting this software development approach. The main reason is the scarcity of adequate, easy to use, and useful tools. Developers typically write code and test it. These tests usually consist of executing the program and checking its output against its requirements. This, however, is not always an exhaustive discipline. On the other side, using formal methods one might be able to investigate the system s properties further. Unfortunately, specification languages do not always have tools like animators or simulators, and sometimes there are no friendly Graphical User Interfaces. On the other hand, specification languages usually have a compiler which normally generates a Labeled Transition System (LTS). This work proposes an application that provides graphical animation for formal specifications using the LTS as input. The application initially supports the languages B, CSP, and Z. However, using a LTS in a specified XML format, it is possible to animate further languages. Additionally, the tool provides traces visualization, the choices the user did, in a graphical tree. The intention is to improve the comprehension of a specification by providing information about errors and animating it, as the developers do for programming languages, such as Java and C++.